River, coastal and estuarine morphodynamics : RCEM 2005 : proceedings of the 4th IAHR Symposium on River, Coastal and Estuarine Morphodynamics, 4-7 October 2005, Urbana, Illinois, USA /: RCEM 2005 : proceedings of the 4th IAHR Symposium on River, Coastal and Estuarine Morphodynamics, 4-7 October 2005, Urbana, Illinois, USA. Volume 1 ([2006]) - Unknown
No abstract available